2017
DOI: 10.47566/2017_syv30_1-020021
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a combined silver nanoparticles/fluoride varnish in dental remineralization in children: in vivo study

Abstract: Dental caries is an infectious disease that can occur in children, sometimes as soon as the teeth eruption starts. Nanotechnology provides effective strategies in prevention and treatment of dental caries. The purpose of this study was to determine the effectiveness of the addition of silver nanoparticles to a fluoride varnish for the remineralization of primary teeth with white spot lesions. A trial was carried out in children with dental demineralization (white spot lesions) on both maxillary dental teeth. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…Meanwhile, the obtained results revealed that the percent increase in F ion content had significantly occured in NSSF group after intervention in comparison to other remineralizing groups. This may be because of the synergistic effect of nanosilver particles to fluoride, thus enhancing remineralization of early carious lesions (30). The results of the present study are in accordance with Silva et al (31) who concluded that both NSF fluoride and NaF varnish were effective in remineralizing primary teeth enamel through Optical Coherence Tomography (OCT).…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, the obtained results revealed that the percent increase in F ion content had significantly occured in NSSF group after intervention in comparison to other remineralizing groups. This may be because of the synergistic effect of nanosilver particles to fluoride, thus enhancing remineralization of early carious lesions (30). The results of the present study are in accordance with Silva et al (31) who concluded that both NSF fluoride and NaF varnish were effective in remineralizing primary teeth enamel through Optical Coherence Tomography (OCT).…”
Section: Discussionsupporting
confidence: 91%
“…Another study conducted in 130 decayed deciduous teeth of children treated with NSF and control (water), 81% of teeth in the NSF group had halted carious lesions on day 7, 72.7% after 5 months and 66.7% of lesions were still arrested after a year, whereas the control group had 0%, 27.4% and 34.7% respectively (dos . In yet another study conducted in 22 children aged 1-6 years with white spot lesions detected by baseline DIAGNOdent values were treated with the fluoride plus 0.1% AgNPs and the children in control group were treated with commercial fluoride varnish once a week for a 3 weeks and after 3 months follow-up DIAGNOdent measurements were taken and it was found that teeth coated with AgNPs varnish exhibited lower mean fluorescence intensity than those treated generic varnish, indicating that dental remineralization was higher in this group (Butrón-Téllez Girón et al, 2017). Tirupathi et al tested the therapeutic caries arresting potency of a prepared 5% silver nanoparticles introduced Sodium fluoride (NSF) varnish with commercially available thirty eight percent SDF in 159 primary molars in 50 children for a year and showed similar number of active and arrested caries.…”
Section: Therapeutic Use Of Nano Silver Fluoride In Dental Caries Man...mentioning
confidence: 99%
“…Nano-silver uoride (NSF) varnishes have been developed with high remineralization property and antimicrobial effect (3) . Primary teeth treated with uoride varnish with silver nano-particles have improved dental structure than those treated with conventional varnish following remineralization of early WSLs (4) . Nano-silver mouthwash has been proved to be more effective than NaF mouthwash in reducing WSLs in permenant teeth after six months follow-up (5) .…”
Section: Introductionmentioning
confidence: 97%